Effect of P-glycoprotein Inhibitor (Carvedilol) on Developmental Outcome Methotrexate are Given Alone and in Combination of Pregnant Rats - Shnawa, Zaid K; Abass, Duraid A (The Iraqi Journal of Veterinary Medicine, 2022)
This study was performed according to FDA protocol to evaluate the developmental effects of carvedilol (P-glycoprotein inhibitor), methotrexate (P-glycoprotein substrate) and their combination at therapeutic doses on pregnant rats. Sixty Albino Wistar rats (40 female rats and 20 males) were allocated randomly into four groups orally administered 0.72 mg/kg carvedilol (Cv-treated group [TG]), 0.36 mg/kg methotrexate (MTX-TG), combined doses carvedilol+methotrexate (Cv+MTX-TG), and distilled water (control group) for 2 months in male and 2 weeks in female rats before mating and after copulation, then approval of pregnancy; dosing continued in female groups during pregnancy and lactation periods. Half of the animal groups were euthanized one day before parturition to study prenatal effects, while the other half left for parturition and lactation to study postnatal effect. The results of fertility index recorded in Cv-TG (71.43%), MTX-TG (42.46%) and Cv+MTX-TG (38.47%) was markedly lower than that in control (83.33%) group with lower gestation index was recorded in MTX-TG (80%) and Cv+MTX-TG (60%) than that in Cv-TG (100%) and the control group (100%). The result of resorbed and fetal death recorded a higher percent in Cv-MTX-TG in comparison with MTX-TG and Cv-TG; Cv-MTX-TG fetuses also recorded more anomalies, including hemorrhagic placenta, curved legs, and microcephaly during prenatal period. The postnatal effects showed that the Cv+MTX-TG group recorded a higher decrease in number of pups born, their weight, and increase in number of stillbirths in comparison with methotrexate followed by carvedilol groups in comparison with control group, while the result of viability index recorded (Cv-TG=98.15%, MTX-TG=93.93% and Cv+MTX-TG=76.19%) and lactation index (Cv-TG=77.36%, 83.87% and Cv+MTX-TG=75%). The postnatal anomalies were only recorded in Cv+MTX-TG included skull defect and ulceration, blindness, skin lesion, and alopecia in lactating pups. It is concluded that inhibition of P-gp by carvedilol might increase the placental passage and increase methotrexate concentration in fetal and pups’ tissue with consequence of increase toxic effect of methotrexate both in fetus and pups of Cv+MTX-TG group which might explain the present results of teratogenic study.